High-performance yttrium-iron alloy doped Pt-free catalysts on graphene for hydrogen evolution. Issue 71 (6th December 2018) - Zhu, Pengcheng; Lyu, Dandan; Shen, Pei Kang
Abstract : Research into the preparation and application of metal/graphene nanocomposite materials is an important issue in the field of graphene applications. Abstract : Research into the preparation and application of metal/graphene nanocomposite materials is an important issue in the field of graphene applications. Metal nanomaterials and graphene materials have many excellent properties and have been perfectly combined into metal/graphene nanocomposite materials. These offer the high catalytic activity of metal nanomaterials and the high specific surface area and favorable electrical conductivity of graphene. The unique advantages can produce synergistic effects and can significantly improve the overall performance of the composite materials. This gives the metal/graphene nanocomposite materials excellent application prospects for hydrogen evolution. Here, we report the preparation of yttrium-doped palladium/iron on graphene (Pd/YFeO3 / G C) using a simple and efficient method. The catalytic performance of the Pd/YFeO3 / G C nanocomposites for water electrolysis and hydrogen production was evaluated. The results show that the overpotential for the hydrogen evolution reaction at −10 mA cm −2 is only 15 mV, which is competitive with Pt/C catalysts. The Pd/YFeO3 / G C is highly active for hydrogen evolution with an onset potential of −8 mV in 0.5 M H2 SO4 solution and a Tafel slope of 37 mV dec −1 with a Pd loading of only 20 μgPd cm −2 . These results clearly demonstrated that Pd/YFeO3 / G C is an excellent catalyst for hydrogen evolution.